How do banking crises affect aggregate consumption? Evidence from international crisis episodes - Petra Gerlach-Kristen; Brian O'Connell; Conor O'Toole (The Economic and Social Research Institute (ESRI), 2013)
This paper considers the effect of systemic financial crises on aggregate consumption. Using a sample of 23 countries over 32 years, we find that consumption growth seems lower during banking crises, crises following credit booms and crises following house price booms. Moreover, the response to income growth seems to change, which may be due to credit constraints. In the long run, consumption appears to be linked to income, housing and other financial wealth.
Keywords: 330; Financial Crises; Consumption; Housing Wealth; Panel Error Correction Model; Weak Exogeneity